EFFECT OF MENSTRUATION ON TEAR PRODUCTION AMONG UNDERGRADUATE STUDENTS OF MADONNA UNIVERSITY, ELELE CAMPUS, RIVERS STATE NIGERIA - Oboh, Roland A; Onwukwe, Nnaemeka A; Mube, William A; Uzoechi , Nneoma C (International Journal of Health, Medicine and Nursing Practice, 2021)
Purpose: The menstrual cycle has been reported to influence many other physiological processes in women. This study ascertained the effect of menstruation on oculovisual status with emphasis on tear production among young female undergraduates of Madonna University, Elele Campus Rivers State Nigeria. Methodology: The study involved 103 female undergraduates with fairly regular menstrual cycle selected through convenience sampling technique. Their age ranged from 16-30 years with a mean age of 20.82 ± 3.205 years and a median age of 20 years. A well-structured interviewer administered questionnaire was used to elicit oculovisual symptoms associated with the menstrual cycle. Schirmer's test strip was used to measure tear volume at pre-determined intervals of the menstrual flow period. External and internal eye examinations were also carried out using the Pen torch and ophthalmoscope respectively. Data collected were analysed using the Statistical Package for Social Sciences (SPSS) version 21 and results were expressed using tables and correlation of variables expressed using Dunnett's multiple comparison test. Findings: There was a significant increase (p Ë‚ 0.05) in tear production during the first two days of the flow and a slight decrease during the last two days. Comparison of the right and left eyes showed no statistically significant (p Ëƒ 0.05) difference. Variation in tear production associated with menstruation with respect to age showed statistically significant (p Ë‚ 0.05) differences for all age groups except for the right eye of subjects within age group 26-30 years. While 52.4% (n=54 ) of the ladies have no oculovisual complaint, the most common oculovisual complaint was headache 42.7% (n = 44) followed by blurry vision 2.91 % (n = 3) and excessive tearing 1.94% (n = 2). Contribution to Knowledge: The study revealed that physiological changes likely resulting from hormonal variation during the menstrual flow influences tear volume and may cause visual discomfort among women within the reproductive age and recommended the need for tear volume assessment and detailed case history prior to management of complaints associated with dry eye and dispensing of contact lenses for pre and post-menopausal women.